Efek fly ash terhadap parameter kompaksi material komposit lapisan base course suatu hauling road - Immanuel Marchellino; Andrias Suhendra Nugraha (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
The utilization of coal combustion waste, particularly fly ash (FA), as an additive in the base course of mining haul roads has the potential to enhance the mechanical performance of the material while supporting sustainable construction practices. This study aims to analyse the effect of fly ash on Maximum Dry Density (MDD) and Optimum Moisture Content (OMC) in a composite material of fly ash and fill material (FM). Samples were collected from the PLTU stockpile in the Tanjung Selor mining area, North Kalimantan, and compaction tests were conducted in the laboratory using the Standard Proctor method (ASTM D698). The results indicate that pure fly ash has a low MDD (0.94 t/m³) and high OMC (65%) due to its fine, lightweight, and porous particles. The addition of 35% fly ash to 65% fill material significantly increased MDD to 1.62 t/m³ and reduced OMC to 10%, demonstrating the interstitial filling effect that improves composite density. Fly ash is non-plastic with a specific gravity (Gs) of 3.02, enhancing the mechanical stability of the composite material without causing plastic deformation. The study concludes that a 35% fly ash proportion in the base course achieves an optimal balance between high density, low moisture content, and ease of compaction, while promoting sustainable mining infrastructure through industrial waste reduction and material cost efficiency.